Human Resource Management Strategy in Facing Organizational Change - Rio Mattajang (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
Organizational change is an inevitable phenomenon in the dynamic business world, and HR management has a crucial role in facilitating successful adaptation to such changes. This research aims to investigate effective human resource management (HR) strategies in facing organizational change. This research uses a qualitative approach with descriptive methods. The research results show that in facing organizational change, human resource management (HR) plays a crucial role in ensuring effective adaptation. Challenges such as lack of leadership support, resistance to change, lack of resources, and global expansion came into focus. A holistic and strategic approach is needed in designing and implementing HR strategies that support organizational strategic change. This includes thorough evaluation, effective allocation of resources, and involving key stakeholders. Thus, effective and focused human resource management is key in helping organizations face change successfully and achieve their long-term goals.